Effect of Different Levels of Nitrogen Intake on the Chemical Composition of Grain and Husk of Local and Hybrid Varieties of Oryza sativa - Vijay Singh, Ran; Singh, R.K.; Singh, Dhirendra (Asian Journal of Chemistry, 2010)
Rice is a staple diet of Indian people especially in some of the thickly populated regions of the country. The agricultural scientists have been successful in producing high yielding hybrid varieties of rice and the producing of rice has been considerably increased. But little attention seems to have been paid to the nutritive values of these varieties. Nitrogen supply commonly limits grain yield in irrigated rice systems. The demand of the rice plant for other macronutrients mainly depends on the N supply. On the other hand, the average and receiving of fertilizer N is only about 30 %. Recently the use of sophisticated nitrifying inhibitors like isobutylidene urea, etc., have been recommended for supplying nitrogen. It is necessary to test the real worth of these costly new fertilizers in comparison to indigenously prepared cheap and slow nitrogen release fertilizers like urea treated with neem or other non-edible cakes, which hold considerable promise for increasing the efficiency of N-fertilization.